The cinema, a strategy to develop critical thinking skills in social - Morantes Cepeda, Sandra Liliana; Gordillo Ávila, Yasmín (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The paper “Films, a strategy to develop critical thinking skills in social sciences” begins of a problem found in first and second grade students of the Manitas campus of the Educational Institution “Álvaro González Santana” (IEPAGS) in Sogamoso (Boyacá, Colombia) in which it was observed that in their daily learning, they did not develop critical thinking skills, such as: comprehension, interpretation and proposition. In order to improve these difficulties, various didactic-pedagogical strategies were used, through films, which allowed them to develop these skills. This research was framed in the action research methodology, with a qualitative approach, which defined the path to follow, in three phases: diagnosis, intervention and analysis and interpretation, facilitating in the students the remembrance, contextualization and the strengthening of their written and oral expression on topics of Social Sciences.